التّوظيف التّراثيّ في شعر أدونيس - حسن, محمد (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
يدرس هذا البحث موضوع "التوظيف التراثي في شعر أدونيس" منطلقاً من الحديث عن ثقافته التراثية, التي أسهمت في بلورة موقفه منه, ومركزاً على توظيف مصادر التراث في إبداعاته الشعرية من: قرآن كريم, وحديث شريف, وأقوال مأثورة, وأمثال, وشخصيات تراثية بأطيافها وألوانها كلها: السياسية, والأدبية, والفنية, والدينية, والأسطورية. وقد أولى البحث الشخصيات التراثية عناية خاصة؛ لأنها تحتل مساحة واسعة من إبداع أدونيس الشعري, كما أبرز البحث تأثر أدونيس بالفكر الصوفي, والأسطوري والتناسخي ولاسيما أسطورة الخصب التي بنى عليها نظريته الفكرية, ومشروعه الحضاري في الهدم والبناء, والدعوة إلى التجاوز والتخطي. وقد انتهى البحث إلى خاتمة تلخص أهم النتائج التي توصّل إليها الباحث, مع ثبت للمصادر والمراجع التي اعتمد عليها. This article tackles the question of tradition and its functional use in Adonis' poetry, starting with his traditional education that contributed to crystallizing his position on this matter; I have paid special attention to Adonis' employment of various traditional sources in his poetic creations like Quran, Hadith, sayings, proverbs, and traditional characters from all fields, be they political, literary, religious, and mythical. Traditional characters have also been given special prominence because they occupy a wide range in Adonis' Poetic creativity. The article has also demonstrated Adonis' indebtedness to Sufism, myth, and reincarnation, with special reference to fertility myths on which he built his theory of construction and deconstruction and his call for transcendence. The conclusion summarizes the most important points, ending with a list of works cited by the researcher.